Kampong Bharu AR - Farah Nellysa Najwa Musa; Fadzillah Binti Abd Aziz (Journal of Computing Technologies and Creative Content, 2022)
AR is an emerging technology that enables people to experience a whole new world through their smartphones. This technology can be utilized for various industries such as education, gaming, and tourism. This Augmented Reality (AR) application is suitable for all ages and makes it easy for tourists to find out more about Kampong Bharu. The waterfall model is used in this research, which includes Requirements, Analysis, Design, Implementation, Testing, Deployment, and Maintenance. The focus of this research is to figure out how to make it simpler and more participatory for visitors to learn about and describe Kampong Bharu. As a result, the findings indicate that tourists will alter their typical mode of transportation before or after the trip. This Augmented Reality (AR) software will assist travelers in making decisions on their route to Kampong Bharu. Visitors have a great opportunity to explore the Kampong Bharu region since Augmented Reality (AR) applications make it simple to obtain information.